Creating individual level air pollution exposures in an anonymised data safe haven: a platform for evaluating impact on educational attainment. (2018) - Mizen, Amy; Lyons, Jane; Doherty, Ruth; Berridge, Damon; Wilkinson, Paul; Milojevic, Ai; Carruthers, David; Akbari, Ashley; Lake, Iain; Davies, Gwyneth; Mavrogianni, Anna; Sallakh, Mohammad Al; et al.
No abstract available